2015 International Conference on Information and Digital Technologies 2015
DOI: 10.1109/dt.2015.7222967
|View full text |Cite
|
Sign up to set email alerts
|

Applications, energy consumption, and measurement

Abstract: Abstract-The task of reducing the energy footprint of IT devices and software has been a challenge for Green IT research. Monitoring approaches have primarily focused on measuring the energy consumption of the hardware components of computing devices. The use of applications or software on our computer systems consumes energy and it also affects how various hardware components and system resources consume energy. Consequently, running web browsers applications will utilise considerable energy and battery consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…To evaluate Unit Energy Consumption we can monitor the following hardware resources [14]: Hard disk: disk bytes/sec, disk read bytes/sec, disk write bytes/sec Processor: % processor usage Memory: private bytes, working set, private working set Network: bytes total/sec, bytes sent/sec, bytes received/sec IO: IO data (bytes/sec), IO read (bytes/sec), IO write (bytes/sec) Attributing some weights to elements of the UEC or by some reliable assumption such as considering the power model to be linear in nature for each individual component, We can compute the SEC Metric.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate Unit Energy Consumption we can monitor the following hardware resources [14]: Hard disk: disk bytes/sec, disk read bytes/sec, disk write bytes/sec Processor: % processor usage Memory: private bytes, working set, private working set Network: bytes total/sec, bytes sent/sec, bytes received/sec IO: IO data (bytes/sec), IO read (bytes/sec), IO write (bytes/sec) Attributing some weights to elements of the UEC or by some reliable assumption such as considering the power model to be linear in nature for each individual component, We can compute the SEC Metric.…”
Section: Resultsmentioning
confidence: 99%
“…Modelling the energy consumption of applications, gathering valid data from active and passive application processes (i.e., applications in focus and idle applications) is a crucial activity which can be used to find correlations and trends in various areas of research such as developer's productivity, applications with the highest energy consumption profiles and more. To this aim, researchers have proposed hardware-based tools as well as model-based [13] and software-based [14] techniques to approximate the actual energy profile of applications. However, all these solutions present their own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these hardware specifications, Joulemeter 1.2 was the ideal candidate to quantitatively measure and gather program execution duration and energy usage data. This tool is Windows-friendly, easy to use, and provides detailed data on the CPU, software applications, and the monitor (Kor et al, 2015).…”
Section: Micro Methodologymentioning
confidence: 99%
“…A piece of software is labeled as green or energy-efficient when it consumes less energy for its efficient computation that results in minimal adverse effects on environment [51]. Several research work has been conducted on the investigation of energy efficiency of web-based software application [52] and software features [53]. The direct impact of software on a laptop or mobile battery can easily be measured as approximately 25% to 40% of the total energy consumed by a device [54].…”
Section: Energy-efficient Softwarementioning
confidence: 99%
“…4, it can be observed that the energy consumption of hardware that runs the application is much higher compared to the energy consumed by the application for each algorithm. In order to facilitate the reduction of the overall energy consumption, more research and investigation need to focus on the optimization of interaction and processes between hardware and software [52].…”
Section: Energy Consumptionmentioning
confidence: 99%